2010
DOI: 10.1159/000318570
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Ageing: Neurological Issues

Abstract: nervous system as a whole, and in particular on the CNS. During cerebral development, vitamin D may act like a neurosteroid hormone in the areas of neurotrans mission, neuroprotection, and neuroimmunomodulation. Moreover, vitamin D deficiency has been associated with neurological and psychiatric disorders. In older adults, hypovitaminosis D has been associated with neuromuscular disorders, dementia, and Parkinson's disease. Thus, vitamin D supplementation might have a protective effect against these neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
202
1
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 210 publications
(218 citation statements)
references
References 226 publications
5
202
1
10
Order By: Relevance
“…Various neuroprotective effects of vitamin D in the CNS and the eye may explain these associations. In vitro, vitamin D increases the synthesis of neurotrophic agents such as the Nerve Growth Factor (NGF) and the Glial cell lineDerived Neurotrophic Factor (GDNF), and regulates neuronal differentiation and maturation [26,27]. It also accelerates neuronal growth in a dose-dependent way in rat hippocampal cell cultures [28].…”
Section: Discussionmentioning
confidence: 99%
“…Various neuroprotective effects of vitamin D in the CNS and the eye may explain these associations. In vitro, vitamin D increases the synthesis of neurotrophic agents such as the Nerve Growth Factor (NGF) and the Glial cell lineDerived Neurotrophic Factor (GDNF), and regulates neuronal differentiation and maturation [26,27]. It also accelerates neuronal growth in a dose-dependent way in rat hippocampal cell cultures [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our results differ from 2 other published systematic reviews of vitamin D and cognitive performance. 10,11 Barnard and Colon-Emeric 11 suggested that cognitive function measured by MMSE was not associated with 25(OH)D concentration although their conclusions were based on whether the relationship between vitamin D and cognitive test scores in the original studies was statistically significant. Since statistical significance depends on sample size, solely focusing on this criterion could mask a small consistent effect in underpowered studies.…”
mentioning
confidence: 99%
“…9 Two recent systematic reviews examined the association between vitamin D and cognitive performance, 10,11 but found insufficient evidence to make a conclusion. Both studies were limited in their scope of study inclusion, and provided no meta-analysis.…”
mentioning
confidence: 99%
“…there is loss of buffering ability, and wide excursions of pressure and heart rate) leading to an inappropriate adaptive response to standing up. 26 Vitamin D metabolites regulate the genetic expression of neurotrophins (nerve growth factor and neurotransmitters) with a consequent reduction in appropriate compensatory mechanisms during standing up. 27,28 Third, another explanation relies on the fact that hypovitaminosis D could be involved in increasing blood pressure levels which may result in the prescription of antihypertensive drugs and consequent greater risk of iatrogenic OH.…”
Section: Discussionmentioning
confidence: 99%